Exploring the Experiences of the Teaching-Learning Process of Mazandaran University of Medical Sciences Officials During the Covid-19 Pandemic: Challenges and Strategies - Fahimeh Ghasemi Charati; Ali Hesamzadeh; Mahsa Kamali; Farhad Gholami; Pedram Ebrahimnejad; Mahmood Moosazadeh; Fereshteh Araghian Mojarrad; Masoumeh Bagheri-Nesami (Majallah-i dānishgāh-i ulū m-i pizishkī Māzandarān, 2024)
Background and Purpose: Shortly after the emergence of COVID-19, the World Health Organization declared it a pandemic, which brought numerous challenges to the field of education worldwide. Consequently, this study was conducted to explore the teaching and learning processes of officials during the pandemic. Materials and Methods: This qualitative research study was conducted using a comprehensive content analysis approach from April to November 2023. The participants included 11 officials from Mazandaran University of Medical Sciences, specializing in the teaching and learning process, who were selected purposefully. Data were collected through semi-structured individual interviews and by evaluating documents from the university's directorate and vice-chancellor. To ensure the validity of the qualitative study, four criteria—credibility, confirmability, dependability, and transferability—were employed. Credibility was established through prolonged engagement and sufficient interaction with participants, gathering accurate information, and validating it with participants. Dependability was ensured through peer review by two qualitative research experts, who confirmed the validity of the data analysis process. Confirmability was obtained through the perspectives of the research team colleagues. All research processes were documented and reported in detail to ensure the transferability of the results. Results: From the in-depth analysis of interviews and documents, 520 initial codes were extracted. After reviewing and summarizing the codes multiple times, they were classified based on similarities and correlations. The underlying meanings were identified through analysis and comparison, and the codes were conceptually and abstractly named based on their nature. Ultimately, two main categories, "challenges" and "strategies," emerged from the process of code abstraction. The "challenges" category was derived from three sub-categories: psychosocial pressures, challenges in theoretical teaching, and challenges in clinical education. The "strategies" category evolved from eight sub-categories: strategies to improve virtual teaching of theoretical courses, strategies to improve clinical and practical teaching, the formation of virtual groups for students and enhanced communication with them, managing the physical presence of students and professors according to the pandemic situation, providing facilities for students to access virtual education content, emerging educational strategies, facilitating educational regulations with increased flexibility, and providing the necessary resources to adhere to in-person education protocols. Conclusion: The COVID-19 pandemic introduced various challenges for both professors in adapting their teaching methods and students in adjusting to online learning. However, these challenges also presented opportunities. The pandemic forced changes in educational processes, providing a new experience or opportunity to learn, understand, and adapt to the evolving needs of medical education for all stakeholders. These changes may also have long-term impacts on healthcare. The experiences gained during the pandemic can be used to revise health-related policies, and documenting these experiences can help in better managing future epidemics.